2006
DOI: 10.1021/bi060183n
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the tRNA A76 Hydroxyl Groups throughout Translation

Abstract: The free 2'-3' cis-diol at the 3'-terminus of tRNA provides a unique juxtaposition of functional groups that play critical roles during protein synthesis. The translation process involves universally conserved chemistry at almost every stage of this multistep procedure, and the 2'- and 3'-OHs are in the immediate vicinity of chemistry at each step. The cis-diol contribution affects steps ranging from tRNA aminoacylation to peptide bond formation. The contributions have been studied in assays related to transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 92 publications
(111 reference statements)
1
47
0
3
Order By: Relevance
“…The spontaneous hydrolysis rate of Tyr-3Ј-dA76 tRNA Phe was Ϸ5-fold slower than those of Tyr-3Ј-A76 tRNA Phe and Tyr-3Ј-F-A76 tRNA Phe (Fig. 7C) probably because of the inductive effects (ϪI) of the electronegative hydroxyl and fluoride groups, which destabilize the aa-tRNA by withdrawing electrons from the ester linkage (22). (31) and LeuRS (32) did not identify catalytic residues.…”
Section: Figmentioning
confidence: 98%
See 1 more Smart Citation
“…The spontaneous hydrolysis rate of Tyr-3Ј-dA76 tRNA Phe was Ϸ5-fold slower than those of Tyr-3Ј-A76 tRNA Phe and Tyr-3Ј-F-A76 tRNA Phe (Fig. 7C) probably because of the inductive effects (ϪI) of the electronegative hydroxyl and fluoride groups, which destabilize the aa-tRNA by withdrawing electrons from the ester linkage (22). (31) and LeuRS (32) did not identify catalytic residues.…”
Section: Figmentioning
confidence: 98%
“…9, discussed in ref. 22). In contrast, structural studies of the ThrRS editing site suggested that two water molecules are specifically activated by editing site residues and subsequently hydrolyze the posttransfer editing substrate (18).…”
mentioning
confidence: 99%
“…However, PheRS proved to be a competitor with EF-Tu for Tyr-tRNA Phe , resulting in the rebinding of the mischarged species at the editing site. Notice that EF-Tu also acts as an isomerase, using a mixture of the 2′(3′)-aminoacyl tRNA isomers as a substrate, and converting them to uniform 3′ complexes (28,29,34). Therefore, the editing site of PheRS has to be in a position to hydrolyze either the 2′-or 3′-OH misacylated tRNA species.…”
Section: Discussionmentioning
confidence: 99%
“…Elongation of the polypeptide chain on the ribosome occurs at a faster rate (by 15-20 s −1 ) than spontaneous acyl migration (29). Not considered as a rate-limiting step in chain elongation, the joint activities of transacylation and hydrolysis should keep the supply of charged tRNA ahead of its transportation to the ribosomal peptidyl transferase center with EF-Tu.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation